Globalny system akademicki i stratyfikująca rola badań naukowych - Kwiek, Marek (Człowiek i Społeczeństwo, 2021)
The global stratification of higher education institutions is accompanied by the vertical differentiation of the academic profession. The various segments of the profession and the various components of higher education systems have been drifting apart. A general contrast emerges between the haves and have-nots in terms of working conditions and the attractiveness of the academic profession at the individual level; and the global visibility in league tables and access to national research funding at the institutional level. In massified systems, the traditional teaching-research nexus will be maintained in practice almost exclusively in the small elite sub-sector. The opportunities at the disposal of institutions will vary immensely in the future, but the most important, qualitative distinction will be between the top 1,000 universities and the rest (comprising about 25,000–30,000 institutions).